Peripampasic Arc: a route of dispersion for lichens - GARCÍA,RENATO A. (2021)
Abstract The Peripampasic Arc is a set of low mountains / hills that connects the Andes, as it scatters to the East forming mountainous areas of lower heights in north-eastern Argentina, with the Atlantic coastal range of the Serra do Mar in Brazil. Numerous studies proved its important biogeographic connection for plant and animal phylogenies, but no information of this pattern is known to lichens. The aim of this work is to establish if the dispersion route of the lichenbiota follows the previously known Peripampasic Arc. For this reason, a comparative study of each area regarding its similarities was analyzed, with emphasis on the biota of the Buenos Aires’ Sierras. We quantified the similarity and β diversity of 104 saxicolous lichens species. There was a strong similarity between the Sierra de la Ventana and Tandil biota, which in turn is linked to the biotas of Uruguay, the Pampean Sierras and the northwest of Argentina. The lack of subgroups in the Peripampasic Arc implies the arc acts as a functional unit of dispersion, which is the most likely cause for the present lichens’ distribution.